2023
DOI: 10.1002/jat.4469
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress‐mediated epidermal growth factor receptor activation by cigarette smoke or heated tobacco aerosol in human primary bronchial epithelial cells from multiple donors

Abstract: The epidermal growth factor receptor (EGFR) signaling pathway has essential roles in maintaining homeostasis of various tissues by regulating cell proliferation and differentiation. Deregulation of the EGFR signaling pathway is associated with various chronic diseases including chronic obstructive pulmonary disease. Cigarette smoke (CS) is known to activate EGFR, which is linked to chronic obstructive pulmonary disease. The biological sequence from CS exposure to EGFR activation is initiated by oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…2 Furthermore, it has been demonstrated that EGF (Epidermal Growth Factor) is produced in epithelial cells in response to smoke and that further increases the possibility of metaplastic as well as hyperplastic changes. 5 Therefore, we suggest that there exists a strong relation between exposure to cigarette smoke and the development of metaplastic meibomian gland dysfunction. Further studies in this regard might help in prevention, as well as newer diagnostic approaches towards MGD especially in populations exposed to cigarette smoke on a regular basis.…”
Section: Open Access J Pak Med Assocmentioning
confidence: 86%
“…2 Furthermore, it has been demonstrated that EGF (Epidermal Growth Factor) is produced in epithelial cells in response to smoke and that further increases the possibility of metaplastic as well as hyperplastic changes. 5 Therefore, we suggest that there exists a strong relation between exposure to cigarette smoke and the development of metaplastic meibomian gland dysfunction. Further studies in this regard might help in prevention, as well as newer diagnostic approaches towards MGD especially in populations exposed to cigarette smoke on a regular basis.…”
Section: Open Access J Pak Med Assocmentioning
confidence: 86%
“…Four articles were identified that utilized fractionated sampling liquid extracts to compare the in vitro effects of HTPs with cigarettes on respiratory tract cell lines [79][80][81][82]. In the first study, the gas-vapor phase of mainstream smoke from three 3R4F Kentucky reference cigarettes and of aerosol from six IQOS HTP consumables was bubbled into PBS to produce extracts [79].…”
Section: Cell Lines Modeling the Respiratory Tractmentioning
confidence: 99%
“…ROS were detected in the emissions from them [ 216 , 217 ]. These emissions have the potential to incite ROS production in cells, with NOX and mitochondria acting as cellular sources for ROS [ 218 , 219 , 220 , 221 , 222 ]. However, there appears to be a distinction in the quantitative aspect of their capacity to induce ROS formation.…”
Section: Additional Issues and Perspectivesmentioning
confidence: 99%
“…In the comparative studies, emissions from HTPs were found to contain a lower quantity of ROS compared to CS [ 79 ], and both HTPs and E-cigarettes demonstrated a lower ability to stimulate cells to produce ROS compared to conventional cigarettes [ 220 , 223 , 224 , 225 , 226 ]. Nevertheless, E-cigarettes induced a comparable alteration in oxidative stress makers to CS in mice studies [ 227 ].…”
Section: Additional Issues and Perspectivesmentioning
confidence: 99%